HISTOPATHOLOGICAL DESCRIPTION OF OCULAR VASCULAR IN ALLOXAN-INDUCED DIABETIC RATS FED FREEZE-DRIED SOYGHURT - Noneng Nawangsih, Eka; Nathalie Margaretha, Shanice; Diantinia (Fakultas Kedokteran Gigi Unjani, 2024)
Diabetes mellitus is a metabolic disease that can cause hyperglycemia (elevated blood sugar levels). Diabetes can cause various complications, one of which is microangiopathy, which is damage to the vascularization of the eye. Soyghurt is a probiotic drink high in isoflavones, has preventive benefits, and can be a supplement for patients with diabetes. This study aimed to determine the vascularization picture of the eye in alloxan-induced diabetic rats and given freeze-dried soyghurt. This study is a descriptive research using Posttest Only Control Group Design. The subjects of this study were white rats (Rattus norvegicus) Wistar strain, which were randomly separated into five groups, namely, three treatment groups and two control groups. Data were analyzed descriptively by describing eye vascularization assessment based on the formation of microaneurysms, hard exudates, cotton-wool spots, dot-blot & flame hemorrhages, and neovascularization. The data processing results showed that the treatment group given a combination of freeze-dried soyghurt and metformin had the highest reduction in sugar levels in diabetic rats, with an average difference of 221.5 mg/dl. The administration of alloxan at a dose of 125 mg/kg of body weight for one day did not change the histopathological picture of eye vascularization in diabetic rats. Further tests need to be conducted regarding the appropriate dose and duration of alloxan administration to see the histopathological picture of eye vascularization damage. DOI : 10.54052/jhds.v4n2.p127-136